THU0118 TREATMENT OF RHEUMATOID ARTHRITIS WITH COMBINATION THERAPY USING A BIOLOGIC AGENT AND METHOTREXATE LOWERS THE RISK OF DECREASING KIDNEY FUNCTION COMPARED TO METHOTREXATE MONOTHERAPY. (June 2019) - YUSUKE, MIWA; Yajima, Nobuyuki; Isojima, Sakiko; Yanai, Ryo; Hatano, Mika; Miura, Yoko; Oguro, Nao; Hayashi, Tomoki; Sakurai, Kosuke; Kasama, Tsuyoshi
Abstract : Background: Rheumatoid arthritis (RA) is associated with reduced kidney function, possibly due to chronic inflammation or the use of nephrotoxic therapies. However, little is known about the effects of novel non-nephrotoxic biologic agents (biological disease-modifying antirheumatic drugs [bDMARDs]) on the risk of decreasing kidney function. Objectives: To elucidate the effects of bDMARDs on decreasing kidney function. Methods: We recruited a cohort of 1058 patients with RA from the All Showa University of RA database. The following background factors were analyzed: age, sex, type of bDMARD, methotrexate and prednisolone dosages, use of conventional synthetic DMARDs and nonsteroidal anti-inflammatory drugs, body mass index, smoking history, diabetes status, hypertension status, dyslipidemia status, serum creatinine (Cr) level, CRP level, and matrix metalloproteinase-3 level. Furthermore, we used the simplified disease activity index (SDAI) for the evaluation of the disease activity of RA. The estimated glomerular filtration rate (eGFR) was calculated using the serum Cr level, age, and sex. We divided the patients into two groups according to the treatment, as follows: bDMARD with methotrexate (MTX) treatment (combination) group (744 patients) and MTX monotherapy group (314 patients). The patients followed the same treatment plan for 1 year. Patients who had primary and secondary failures, adverse effects of drugs, and missing data and those who relocated or withdrew from the study were excluded. Propensity scores were calculated based on the following factors: age, sex, prednisolone dosage, MTX dosage, SDAI, Cr level, eGFR, diabetes status, hypertension status, and dyslipidemia status. Overall, 285 patients in each group were identified by propensity score matching. The primary end-points were the eGFR values before treatment and 6 months and 1 year after treatment. Significance was determined using the repeated-measures analysis of variance (ANOVA). Results: The eGFR (mL/min/1.73 m 2 ) decreased from 88.5 ± 21.8 to 86.1 ± 21.5 and 83.7 ± 21.0 at 6 months and 1 year, respectively, in the combination treatment group and from 86.3 ± 37.9 to 79.5 ± 19.1 and 78.5 ± 19.5 at 6 months and 1 year, respectively, in the MTX monotherapy group. No interaction was observed between the groups. A significant difference was observed between the groups (p = 0.0066) and even during the treatment period (p < 0.001) by repeated-measures ANOVA. Conclusion: The decrease in eGFR was smaller in the combination treatment group than in the MTX monotherapy group. bDMARD use may lower the risk of decreasing kidney function in patients with RA. Acknowledgement: Cooperation on data collection: All Showa University in Rheumatoid Arthritis (ASHURA) group Disclosure of Interests: YUSUKE MIWA Grant/research support from: Mitsubishi Tanabe Pharma Corporation and AbbVie CK. Astellas Pharma Inc., Mitsubishi Tanabe Pharma Corporation, AbbVie CK, Pfizer Japan Inc., Chugai Pharmaceutical Co., Ltd., Eizai Co., Ltd, Asahi Kasei Pharm Co., Ltd, YL Biologics Ltd., Japan Blood Products Organization, Ono Pharmaceutical Co., Ltd., Nippon Kayaku Co., Ltd., and Teijin Pharma Ltd. This work was supported by JPJS KAKENHI Grant Number JP17K09324., Nobuyuki Yajima: None declared, Sakiko Isojima: None declared, Ryo Yanai: None declared, Mika Hatano: None declared, Yoko Miura: None declared, Nao Oguro: None declared, Tomoki Hayashi: None declared, Kosuke Sakurai: None declared, Tsuyoshi Kasama: None declared